2010
DOI: 10.1242/jeb.029074
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin elevates but not voluntary wheel running in mice

Abstract: SUMMARYVoluntary activity is a complex trait, comprising both behavioral (motivation, reward) and anatomical/physiological (ability) elements. In the present study, oxygen transport was investigated as a possible limitation to further increases in running by four replicate lines of mice that have been selectively bred for high voluntary wheel running and have reached an apparent selection limit. To increase oxygen transport capacity, erythrocyte density was elevated by the administration of an erythropoietin (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
55
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(62 citation statements)
references
References 102 publications
6
55
1
Order By: Relevance
“…As compared with C mice, HR mice exhibit various anatomical (Garland and Freeman, 2005;Kelly et al, 2006) and physiological differences (Rezende et al, 2006a;Rezende et al, 2006b;Gomes et al, 2009;Meek et al, 2009) that appear to support their 2.5-to 3-fold greater daily wheelrunning distances. Although previous studies have revealed physiological (Dumke et al, 2001;Rezende et al, 2006a;Rezende et al, 2006b;Gomes et al, 2009;Meek et al, 2009;Kolb et al, 2010), morphological (Garland and Freeman, 2005;Kelly et al, 2006) and motivational (Rhodes et al, 2005; Belke and Garland, 2007) components underlying this HR phenotype, the present findings are the first evidence of neuroanatomical changes in the HR lines. [A previous study that quantified volume of the dentate gyrus of the hippocampus found no statistical difference between the HR and C lines (Rhodes et al, 2003a). ]…”
contrasting
confidence: 55%
See 2 more Smart Citations
“…As compared with C mice, HR mice exhibit various anatomical (Garland and Freeman, 2005;Kelly et al, 2006) and physiological differences (Rezende et al, 2006a;Rezende et al, 2006b;Gomes et al, 2009;Meek et al, 2009) that appear to support their 2.5-to 3-fold greater daily wheelrunning distances. Although previous studies have revealed physiological (Dumke et al, 2001;Rezende et al, 2006a;Rezende et al, 2006b;Gomes et al, 2009;Meek et al, 2009;Kolb et al, 2010), morphological (Garland and Freeman, 2005;Kelly et al, 2006) and motivational (Rhodes et al, 2005; Belke and Garland, 2007) components underlying this HR phenotype, the present findings are the first evidence of neuroanatomical changes in the HR lines. [A previous study that quantified volume of the dentate gyrus of the hippocampus found no statistical difference between the HR and C lines (Rhodes et al, 2003a). ]…”
contrasting
confidence: 55%
“…In our laboratory, selection for high voluntary wheel running in outbred laboratory house mice has been ongoing for more than 60 generations, and has resulted in numerous physiological (Girard et al, 2007;Malisch et al, 2008;Gomes et al, 2009;Meek et al, 2009), behavioral (Rhodes et al, 2001Rhodes and Garland, 2003; Belke and Garland, 2007;Meek et al, 2010), and neurobiological (Rhodes et al, 2003a;Rhodes et al, 2003b) changes in four replicate high-runner (HR) lines of mice as compared with four non-selected control (C) lines. Moreover, a recent comparative study demonstrated a positive correlation between brain size and an index of exercise capacity, maximal oxygen consumption (Raichlen and Gordon, 2011), one of the traits that has increased in the HR lines (Rezende et al, 2006b;Kolb et al, 2010). Therefore, in this study we tested whether selective breeding for high voluntary wheel running in house mice has altered their brain size.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…After 10 generations of selection, mice from the four replicate High Runner (HR) lines were running .70% more revolutions per day (on days 5 and 6) as compared with four nonselected control (C) lines (Swallow et al 1998). Wheel running continued to increase in the HR lines until generation 16-28 (depending on line and sex) and remained approximately at those levels through a subsequent 50 generations of selective breeding Swallow et al 2009;Kolb et al 2010;Careau et al 2012Careau et al , 2013.…”
mentioning
confidence: 96%
“…It was hypothesized that the mini-muscle phenotype has functional characteristics that facilitate high levels of wheel running (Garland et al 2002), such as a doubled mass-specific aerobic capacity (Houle-Leroy et al 2003) and increased fatigue resistance in at least some hind-limb muscles (Syme et al 2005). Alternatively, the underlying allele might have pleiotropic effects that act on nonmuscle tissues and organs but still facilitate endurance running (e.g., reduced total body mass and fat mass; increased relative heart, liver, and kidney mass; longer hind-limb bones) (Garland et al 2002;Kelly et al 2006;Hannon et al 2008;Kolb et al 2010). However, at generation 22, wheel running of affected individuals did not differ statistically from those with normal-sized muscles (Garland et al 2002), and the magnitude of response to selection was not systematically higher in the two lines that had the mini-muscle phenotype as compared with the two that did not, indicating that multiple genetic "solutions" are possible in response to selection for high levels of voluntary exercise (Garland et al 2011a;Careau et al 2013).…”
mentioning
confidence: 99%